2020
DOI: 10.1167/tvst.9.6.16
|View full text |Cite
|
Sign up to set email alerts
|

microRNA Expression Profile in the Vitreous of Proliferative Diabetic Retinopathy Patients and Differences from Patients Treated with Anti-VEGF Therapy

Abstract: microRNA expression profile in the vitreous of proliferative diabetic retinopathy patients and differences from patients treated with anti-VEGF therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…For PDR patients who underwent vitrectomy, because of the close connection between neovascularization and retina, it is difficult to completely separate them by vitrectomy alone. Therefore, patients will further suffer from bleeding and iatrogenic retinal breaks for the separation, which leads to high risk of surgery and impairs the optimal therapeutic effect [ 6 8 ]. In terms of pathogenesis, neovascularization is closely related to VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…For PDR patients who underwent vitrectomy, because of the close connection between neovascularization and retina, it is difficult to completely separate them by vitrectomy alone. Therefore, patients will further suffer from bleeding and iatrogenic retinal breaks for the separation, which leads to high risk of surgery and impairs the optimal therapeutic effect [ 6 8 ]. In terms of pathogenesis, neovascularization is closely related to VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis and response to treatment are two of the main points potentially addressed by the liquid biopsy approach. Recently, different studies have reported the response to DME treatment, by means of aqueous and vitreous samples [32,104,105,[111][112][113][114][115][116]. Sohn et al compared the AH concentration of VEGF and inflammatory molecules after the administration of triamcinolone and bevacizumab, showing that the first one was able to reduce several inflammatory molecules (IL-6, IP-10, MCP-1, PDGF-AA) and VEGF concentration, while bevacizumab just reduced VEGF concentration [32].…”
Section: Diabetic Macular Edema and Response To Treatmentmentioning
confidence: 99%
“…In addition to the direct inhibitory effect of miR-200b on VEGF expression in response to diabetes, it may also mediate such effect indirectly via p300, a histone acetylation and transcription coactivator in malignancies, affecting in this way the gene expression of multiple vasoactive genes [122]. A recent cohort study using vitreous samples from PDR patients has revealed that miR-20a-5p, miR-23b-3p, miR-142-3p, miR-185-5p, miR-223-3p, miR-362-5p, and miR-662 expression levels were significantly higher compared to controls (vitreous from non-diabetic patients with macular holes), whereas miR-199a-5p and miR-326 were significantly lower [123]. Interestingly, all six overexpressed miRNAs have been previously described as potentially targeting proteins that are increased in the vitreous during PDR, such as VEGF-A, angiopoietin 2, PDGF-B, and connective tissue growth factor (CTGF).…”
Section: Mirna In Dr: Role In Oxidative Stress and Inflammatory Signamentioning
confidence: 99%
“…Interestingly, all six overexpressed miRNAs have been previously described as potentially targeting proteins that are increased in the vitreous during PDR, such as VEGF-A, angiopoietin 2, PDGF-B, and connective tissue growth factor (CTGF). These authors claimed that the observed increase in miRNA expression can play a role in the regulation of angiogenesis and wound healing processes in the context of PDR, and the interplay between miRNA and their targets may result in a variety of gene expression profiles [123].…”
Section: Mirna In Dr: Role In Oxidative Stress and Inflammatory Signamentioning
confidence: 99%
See 1 more Smart Citation